Identification of membrane anchor polypeptides of Escherichia coli fumarate reductase. - Lemire, B D (American Society for Microbiology (ASM), 1982)
Fumarate reductase of Escherichia coli has been shown to be a membrane-bound enzyme composed of a 69,000-dalton catalytic-flavin-containing subunit and a 27,000-dalton nonheme-iron-containing subunit. Using gene cloning and amplification techniques, we have observed two additional polypeptides encoded by the frd operon, with apparent molecular weights of 15,000 and 14,000, which are expressed when E. coli is grown anaerobically on glycerol plus fumarate. Expression of these two small polypeptides is necessary for the two large subunits to associate with the membrane. The four subunits remain associated in Triton X-100 extracts of the membrane, and a holoenzyme form of fumarate reductase containing one copy of each of the four polypeptides has been isolated. Unlike the well-characterized two-subunit form, the holoenzyme is not dependent on anions for activity and is not labile at alkaline pH. In these respects, it more closely resembles the membrane-bound activity.